E-073 Endovascular Treatment of a Traumatic Middle Meningeal Artery Pseudoaneurysm with Onyx LES: A Case Report and Review of Literature. (26th July 2014) - Mehta, S; Alawi, A; Edgell, R
Abstract : Background: Middle meningeal artery (MMA) pseudoaneurysms are very rare and are most often traumatic. They may present as an epidural or intraparenchymal hematoma (IPH). Very few cases in medical literature exist of such pseudoaneurysms and little is known about the optimal management of this pathology. Surgical repair as well as endovascular treatment with n-Butyl Cyanoacrylate (n-BCA) and detachable coils have been reported. We report the first such case treated with Onyx liquid embolic system (LES). Methods: Case report and review of the literature. Case report: A 51-year-old woman sustained multiple cranio-facial injuries after a fall down the stairs. Upon initial examination she was agitated and unable to follow commands, and required to be intubated and sedated. A head CT showed right sided subdural haemorrhage (SDH) and a left temporal IPH. She also suffered fractures of her left orbital wall, anterior nasal bone, left clavicle and left 1st rib. CT angiogram of the head and neck was normal. She underwent an emergent craniotomy and evacuation of the SDH and an angiogram was performed to evaluate for a potential vascular lesion. The left external carotid artery (ECA) angiogram revealed a pseudoaneurysm with contrast extravazation of the intracranial left middle meningeal artery (Fig1a ). A decision was made to embolise the lesion. A Sceptre XC 4 mm x 7 mm balloon microcatheter was used to select the left MMA through a 6F guide catheter. Microcatheter angiograms were obtained to confirm placement and rule out potentially dangerous anastomoses. Embolization was performed using Onyx 34 LES. The patient tolerated the procedure well and was subsequently extubated. She continued to show improvement during her hospitalization and at the time of discharge her neurologic exam was significant only for a mild expressive aphasia. At the time of follow up angiography after 3 months, her neurologic exam was normal. The follow up angiogram revealed no residual filling of the pseudoaneurysm (Figure 1b ). Discussion: Traumatic pseudoaneurysms of the MMA are rare but serious lesions with a high mortality rate. These may cause epidural as well as intracerebral hematomas. In cases of trauma with intracerebral hematomas, cerebrovascular imaging should also be performed. Our case highlights the utility of catheter angiography even with a normal CT angiogram. Several treatment options have been reported for these lesions including surgical excision, endovascular treatment with detachable coils or nBCA. Our case illustrates the utility of Onyx LES as a safe and efficacious treatment modality in addition. Disclosures: S. Mehta: None. A. Alawi: None. R. Edgell: None.